Whole-Transcriptome Analysis Reveals Autophagy Is Involved in Early Senescence of zj-es Mutant Rice - Sun, Jia; Liang, Weifang; Ye, Shenghai; Chen, Xinyu; Zhou, Yuhang; Lu, Jianfei; Shen, Ying; Wang, Xuming; Zhou, Jie; Yu, Chulang; Yan, Chengqi; Zheng, Bingsong; et al. (Frontiers in Plant Science, 2022)
Senescence is a necessary stage of plant growth and development, and the early senescence of rice will lead to yield reduction and quality decline. However, the mechanisms of rice senescence remain obscure. In this study, we characterized an early-senescence rice mutant, designated zj-es (ZheJing-early senescence), which was derived from the japonica rice cultivar Zhejing22. The mutant zj-es exhibited obvious early-senescence phenotype such as collapsed chloroplast, lesions in leaves, declined fertility, plant dwarf and decreased agronomic traits. The ZJ-ES gene was mapped in a 458 kb-interval between the molecular markers RM5992 and RM5813 on chromosome3, and analysis suggested that ZJ-ES is a novel gene controlling rice early senescence. Subsequently, whole-transcriptome RNA sequencing was performed on zj-es and its wild-type rice in order to study the regulatory mechanism for early senescence. Totally, 10085 differentially expressed mRNAs (DEmRNAs), 1253 differentially expressed lncRNAs (DElncRNAs), and 614 differentially expressed miRNAs (DEmiRNAs) were identified, respectively, in different comparison groups. Based on the weighted gene co-expression network analysis (WGCNA), the co-expression turquoise module was found to be key for the occurrence of rice early senescence. Furthermore, analysis on the competing endogenous RNA (CeRNA) network revealed that 14 lncRNAs possibly regulated 16 co-expressed mRNAs through 8 miRNAs, and enrichment analysis showed that most of the DEmRNAs and targets of DElncRNAs and DEmiRNAs were involved in reactive oxygen species (ROS)-triggered autophagy-related pathways. Further analysis showed that in zj-es, ROS-related enzyme activities were markedly changed, ROS were largely accumulated, autophagosomes were obviously observed, cell death was significantly detected, and lesions were notably appeared in leaves. Totally, combined our results here and remained research, we suggest that ROS-triggered autophagy induces the programmed cell death (PCD) and its coupled early senescence in zj-es mutant rice.